Information Technology on Aqidah Education and Adolescent's Character - Murjani Murjani (CV. ADIBA AISHA AMIRA, 2022)
Moral aqidah education must move quickly, because globalization with its science and technology advances does not care about our readiness to welcome it, we only have one choice to immediately improve and close ranks with all education supporters. What is clear from the several efforts discussed, the most important is the management of Islamic education itself. Therefore, moral aqidah education has an important meaning and role in shaping the behavior of children and adolescents as a whole. Because with this moral aqidah education, children and adolescents are not directed to the achievement of happiness in life in this world, but also to the happiness of life in the hereafter.